Unraveling mutagenic processes influencing the tumor mutational patterns of individuals with constitutional mismatch repair deficiency - Dilys D. Weijers; Snežana Hinić; Emma Kroeze; Mark AJ Gorris; Gerty Schreibelt; Sjors Middelkamp; Arjen R. Mensenkamp; Reno Bladergroen; Kiek Verrijp; Nicoline Hoogerbrugge; Pieter Wesseling; Rachel S. van der Post; et al. (Nature Communications)
Abstract Constitutional mismatch repair deficiency (CMMRD), caused by bi-allelic germline variants in mismatch repair (MMR) genes, is associated with high cancer incidence early in life. A better understanding of mutational processes driving sequential CMMRD tumors can advance optimal treatment. Here, we describe a genomic characterization on a representative collection of CMMRD-associated tumors consisting of 41 tumors from 17 individuals. Mutational patterns in these tumors appear to be influenced by multiple factors, including the affected MMR gene and tumor type. Somatic polymerase proofreading mutations, commonly present in brain tumors, are also found in a T-cell lymphoblastic lymphoma displaying associated mutational patterns. We show prominent mutational patterns in two second primary hematological malignancies after temozolomide treatment. Furthermore, an indel signature, characterized by one-base pair cytosine insertions in cytosine homopolymers, is found in 54% of tumors. In conclusion, analysis of sequential CMMRD tumors reveals diverse mutational patterns influenced by the affected MMR gene, tumor type and treatment history.